2000
DOI: 10.1161/01.res.87.11.e53
|View full text |Cite
|
Sign up to set email alerts
|

Mice With Disrupted BK Channel β1 Subunit Gene Feature Abnormal Ca 2+ Spark/STOC Coupling and Elevated Blood Pressure

Abstract: Large-conductance potassium (BK) channels in vascular smooth muscle cells (VSMCs) sense both changes in membrane potential and in intracellular Ca(2+) concentration. BK channels may serve as negative feedback regulators of vascular tone by linking membrane depolarization and local increases in intracellular Ca(2+) concentration (Ca(2+) sparks) to repolarizing spontaneous transient outward K(+) currents (STOCs). BK channels are composed of channel-forming BKalpha and auxiliary BKbeta1 subunits, which confer to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
328
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(344 citation statements)
references
References 39 publications
12
328
1
Order By: Relevance
“…The consequences of BK channel ablation exceed by far those caused by deletion of the regulatory BK channel ␤ 1 subunit, which is not significantly expressed in neurons and produced no neural effects (33,34). Nevertheless, the BK channels, despite their widespread expression in the CNS (24), appear to play surprisingly modest roles in normal brain function.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of BK channel ablation exceed by far those caused by deletion of the regulatory BK channel ␤ 1 subunit, which is not significantly expressed in neurons and produced no neural effects (33,34). Nevertheless, the BK channels, despite their widespread expression in the CNS (24), appear to play surprisingly modest roles in normal brain function.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data suggest that whereas angiotensin II-mediated increases in Ca 2ϩ entry through L-type Ca 2ϩ channels are necessary for NFAT activation and ␤1 subunit down-regulation, an increase in [Ca 2ϩ ] i by itself is not a sufficient stimulus to decrease expression of this BK channel subunit. (3,7). Thus, it is reasonable to hypothesize that angiotensin II infusion into NFATc3 Ϫ/Ϫ mice would either not increase blood pressure or increase it to a lesser extent than in WT mice (Fig.…”
Section: In Vivo Administration Of Angiotensin II Activates the Calcimentioning
confidence: 94%
“…The functional relevance of the ␤1 subunit of the BK channel was underscored in a recent series of studies, which demonstrated that in ␤1 null mice, arterial smooth muscle BK channels had lower Ca 2ϩ sensitivities than their wild type counterparts. Consequently, these BK channels were decoupled from Ca 2ϩ sparks, which resulted in depolarized arterial smooth muscle, increased vasoconstriction, and ultimately hypertension (3,7).…”
Section: Bkmentioning
confidence: 99%
“…The gene that encodes the β1 subunit of the BK channel is KCNMB1, located on chromosome 5q34. KCNMB1 knockout mice have decreased calcium sensitivity, elevated blood pressure (BP), and cardiac hypertrophy [2,3].…”
Section: Introductionmentioning
confidence: 99%